Vernacular Architecture in Nepal: A Review on Planning and Building Materials - Kandel, Samikshya; Thapa, Luna; Chhetri, Kedar; Baniya, Pragati (Technical Journal, 2024)
Vernacular architecture, deeply rooted in local traditions, stands as a pivotal force in shaping sustainable and climate-responsive building practices. This study aimed to assess the planning, building materials, thermal comfort, and design recommendations presented in seven research articles, focusing on three distinct geographic regions of Nepal. The results emphasized the significance of vertical planning, simple layouts, and the use of local materials, along with the implementation of passive design strategies for thermal comfort. The findings revealed a research gap, pointing to insufficient literature on the topic, particularly in non-hilly regions. The review concludes by emphasizing the practical value of the study for both practitioners and researchers, providing a comprehensive understanding of vernacular architecture in terms of materials and design strategies, and its relevance to contemporary climate responsive design. Additionally, the paper identifies future research directions to further enhance knowledge in this field.